Evaluating the spectrum of histomorphological patterns on endoscopic biopsy in patients with upper gastrointestinal tract disorders - J. Margaret Theresa; Lavanya M.; Dr. J. Gerard Rakesh; K. Sultan Basha (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: The upper gastrointestinal tract (UGT) disorders are more common complaints in clinical practice and have got high degree of mortality and morbidity. Many different types of lesions can affect the upper gastrointestinal tract and can be classified as congenital anomalies, infections, inflammation and neoplastic lesions.Material and Methods: A total of 152 cases of upper gastrointestinal tract biopsies are included in this study, out of which 113 cases were gastric biopsies, 22 cases were esophageal biopsies and the remaining 17 cases were duodenal biopsies. Present study was carried out in the Department of Pathology at Sri Venkateshwaraa Medical College Hospital and Research Centre, Puducherry for a period of one year between March 2018 and February 2019. All the biopsies were performed using fiberoptic endoscopy. Endoscopic biopsy in combination with histopathological examination plays an important role in the early diagnosis of determining UGT lesions. Also, special stains like Giemsa, Warthin starry stain was used to demonstrate Helicobacter pylori. Aim of the study is to evaluate the histomorphological patterns of upper gastrointestinal tract disorders on endoscopic biopsy and to correlate various upper gastrointestinal tract disorders in correspondence to clinical parameters.Results: It is reported among 152 cases of UGT biopsies 137 were non-neoplastic lesions and 15 were neoplastic. Commonly affected age group was 31-40 years followed by 41 to 50 years. As per the present study, males were affected more predominantly than females. Out of the 22 cases from esophageal biopsies, 16 cases showed non-neoplastic lesions and 6 were neoplastic. The most common non-neoplastic lesion was chronic nonspecific esophagitis and neoplastic lesion reported was squamous cell carcinoma. Among 113 gastric biopsies, 104 cases were non-neoplastic lesions and 9 were neoplastic lesions. Adenocarcinoma was the predominant neoplastic lesion of stomach. All the 17 duodenal biopsies showed non -neoplastic lesions.